Three modes of electrochemical impedance spectroscopy measurements performed on vanadium redox flow battery - Krakowiak, Joanna (Elsevier, 2025)
This article presents an innovative approach to monitor working redox flow batteries using dynamic electrochemical impedance spectroscopy, diverging from the commonly sequential impedance methods carried out under potentiostatic or galvanostatic conditions close to the open circle voltage. The authors introduce a fresh variation of dynamic impedance measurement that leverages an amplitude-modulated multi-frequency alternating current perturbation signal. This technique leads to a reduction in measurement time, making it possible to monitor impedance in real-time under typical operational conditions. Consequently, it effectively addresses the limitations stemming from the absence of stationary conditions during impedance measurements. There is no doubt that measurement techniques enabling the study of processes during the operational life of a battery provide the most valuable insights into the properties of these systems. The potential of this proposed approach is exemplified through the examination of a full vanadium redox flow battery as a case study. Classical impedance measurements were also conducted under potentiostatic and galvanostatic conditions with sequential frequency signal change, which requires stopping the battery operation, resulting in electrode potential changes of over 200 mV compared to the working system. Spectra for all modes of measurements were compared. In the case of dynamic measurements, such significant differences in spectra during charging and discharging are not observed, which is characteristic of classical measurements. The authors deliberately and consciously refrain from analyzing the results by fitting equivalent circuits.